Inovasi Pelayanan Publik dalam Pelayanan Pajak Kendaraan Bermotor di Kota Gorontalo - Rendi A. Saleh; Fenti Prihatini Dance Tui; Yacob Noho Nani (Perspektif Administrasi Publik dan hukum, 2026)
Based on the analysis, (1) the support aspect has been implemented effectively, as evidenced by strong leadership commitment, policy support, the availability of facilities and infrastructure, adequate budget allocation, and solid inter-agency coordination, although technical constraints such as network disruptions remain. Further, (2) the capacity aspect is categorized as relatively adequate, reflected in the readiness of human resources, the availability of technological infrastructure, clear standard operating procedures, and the implementation of training programs, despite the need for further enhancement of technical competencies and network quality. Lastly, (3) the value aspect demonstrates highly positive outcomes, as the Warkop Samsat program provides significant benefits, including improved service quality, time and cost efficiency, service convenience, increased user satisfaction, and enhanced public compliance with motor vehicle tax payments In conclusion, public service innovation through the Warkop Samsat program in Gorontalo City has been effectively implemented, generating positive impacts for the community. However, further strengthening of technical aspects and capacity development is required to ensure the program's sustainability.